Comparison of hypertension healthcare outcomes among older people in the USA and England. Issue 3 (23rd November 2015) - Marshall, Alan; Nazroo, James; Feeney, Kevin; Lee, Jinkook; Vanhoutte, Bram; Pendleton, Neil
Abstract : Background: The USA and England have very different health systems. Comparing hypertension care outcomes in each country enables an evaluation of the effectiveness of each system. Method: The English Longitudinal Study of Ageing and the Health and Retirement Survey are used to compare the prevalence of controlled, uncontrolled and undiagnosed hypertension within the hypertensive population (diagnosed or measured within the survey data used) aged 50 years and above in the USA and in England. Results: Controlled hypertension is more prevalent within the hypertensive population in the USA (age 50–64: 0.53 (0.50 to 0.57) and age 65+: 0.51 (0.49 to 0.53)) than in England (age 50–64: 0.45 (0.42 to 0.48) and age 65+: 0.42 (0.40 to 0.45)). This difference is driven by lower undiagnosed hypertension in the USA (age 50–64: 0.18 (0.15–0.21) and age 65+: 0.13 (0.12 to 0.14)) relative to England (age 50–64: 0.26 (0.24 to 0.29) and age 65+: 0.22 (0.20 to 0.24)). The prevalence of uncontrolled hypertension within the hypertensive population is very similar in the USA (age 50–64: 0.29 (0.26 to 0.32) and age 65+: 0.36 (0.34 to 0.38)) and England (age 50–64: 0.29 (0.26 to 0.32) and age 65+: 0.36 (0.34 to 0.39)). Hypertension care outcomes are comparable across US insurance categories. In both countries, undiagnosed hypertension is positively correlated with wealth (ages 50–64). Uncontrolled hypertension declines with rising wealth in the USA. Conclusions: Different diagnostic practices are likely to drive the cross-country differences in undiagnosed hypertension. US government health systems perform at least as well as private healthcare and are more equitable in the distribution of care outcomes. Higher undiagnosed hypertension among the affluent may reflect less frequent medical contact.